Planning ahead: eliciting intentions and beliefs in a public goods game - Luis G. González; Maria Vittoria Levati (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
In a two-person nitely repeated public goods experiment, we use intentions data to interpret individual behavior. Based on a random-utility model specication, we develop a relationship between a player's beliefs about others' behavior and his contributions' plans, and use this relationship to identify the player's most likely preference ype. Our estimation analysis indicates that players are heterogeneous in their preferences also at the intentional level. Moreover, our data show that deviations from intended actions are positively related to changes in beliefs, thereby suggesting that people are able to plan.
Keywords: C70; C72; C92; H41; 330; Public goods games; Experiments; Latent-class logit; Conditional cooperation; Öffentliches Gut; Nichtkooperatives Spiel; Kooperation; Test